Preclinical Assessment of Cardiac Valve Substitutes: Current Status and Considerations for Engineered Tissue Heart Valves - Zhang, Benjamin L.; Bianco, Richard W.; Schoen, Frederick J. (Frontiers in Cardiovascular Medicine, 2019)
Tissue engineered heart valve (TEHV) technology may overcome deficiencies of existing available heart valve substitutes. The pathway by which TEHVs will undergo development and regulatory approval has several challenges. In this communication, we review: 1) the regulatory framework for regulation of medical devices in general and substitute heart valves in particular; 2) the special challenges of preclinical testing using animal models for TEHV, emphasizing the International Standards Organization (ISO) guidelines in document 5840; and 3) considerations that suggest a translational roadmap to move TEHV forward form pre-clinical to clinical studies and clinical implementation.